THE URGENCY OF INDONESIAN LANGUAGE EXTRACURRICULAR ACTIVITIES IN PANCASILA EDUCATION FOR STRENGTHENING THE SENSE OF NATIONALISM AMONG ELEMENTARY SCHOOL STUDENTS - Heri Effendi; Iman Laili; Eriza Nelfi; Puspawati Puspawati; Aimifrina Aimifrina (Study program PGSD FKIP Universitas Bung Hatta, 2026)
This study aims to critically explore the urgency of Indonesian language extracurricular activities in Pancasila education for strengthening the sense of nationalism among elementary school students in Indonesia. Using a qualitative approach through literature analysis, this research examines various international and national academic sources related to the roles of language, school culture, and Pancasila education in shaping national character. The findings indicate that Indonesian language-based extracurricular activities such as debates, speeches, literacy programs, and language-based arts serve as important spaces for the internalization of Pancasila values in a contextual and participatory manner. The integration of the Indonesian language within school culture also strengthens students’ national identity through habitual communication and social interaction that reflect the values of unity, mutual cooperation, and love for the homeland. Furthermore, its relevance within the Merdeka Curriculum and the Pancasila Student Profile highlights that experiential learning approaches effectively enhance students’ cognitive, affective, and psychomotor domains in a balanced way. In conclusion, Indonesian language extracurricular activities represent an effective pedagogical strategy for fostering sustainable nationalism in elementary school students.